Bispecific antibodies for non-Hodgkin’s lymphomas and multiple myeloma - Omar Castaneda-Puglianini; Julio C Chavez (Drugs in Context, 2021)
Immunotherapy has revolutionized the treatment of cancers. There are several approaches, including naked monoclonal antibodies, antibody–drug conjugates, immune-checkpoint inhibitors and chimeric antigen receptor T cell therapies with important success. Bispecific antibodies represent a novel immunotherapeutic approach for the treatment of several malignancies, in particular non-Hodgkin’s lymphoma (NHL) and multiple myeloma (MM). Early-phase studies have shown encouraging clinical activity in poor-risk B cell NHL and MM. Several constructs are currently available and in clinical development for the treatment of these malignancies. Here, we present a narrative review of the most current data on bispecific antibodies in B cell NHL and MM.